2017
DOI: 10.1093/dnares/dsx001
|View full text |Cite
|
Sign up to set email alerts
|

Circadian oscillations of microbial and functional composition in the human salivary microbiome

Abstract: The human microbiomes across the body evidently interact with various signals in response to biogeographical physiological conditions. To understand such interactions in detail, we investigated how the salivary microbiome in the oral cavity would be regulated by host-related signals. Here, we show that the microbial abundance and gene participating in keeping the human salivary microbiome exhibit global circadian rhythm. Analysis of the 16S rRNA sequences of salivary microbial samples of six healthy adults col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 38 publications
4
64
1
1
Order By: Relevance
“…In addition, food timing affected salivary microbiota diurnal rhythms in individual bacterial taxa. Recently, salivary microbiota in the human oral cavity have been shown to exhibit global daily rhythms in both the Firmicutes and Bacteroidetes phyla (59). Consistently, our salivary microbiota results showed similar trends in daily rhythms in the relative abundance of these microbial groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, food timing affected salivary microbiota diurnal rhythms in individual bacterial taxa. Recently, salivary microbiota in the human oral cavity have been shown to exhibit global daily rhythms in both the Firmicutes and Bacteroidetes phyla (59). Consistently, our salivary microbiota results showed similar trends in daily rhythms in the relative abundance of these microbial groups.…”
Section: Discussionmentioning
confidence: 99%
“…The SM has been demonstrated to be individualized [17,18] and temporarily stable [19,20] in orally healthy individuals. On the other hand, circadian oscillations of SM have also been documented [21].…”
Section: The Salivary Microbiota In Oral Healthmentioning
confidence: 99%
“…Given the difficulties to retrieve stool samples around the course of a day, some clinical studies focused on the more accessible human salivary microbiome. These studies showed that abundance and transcriptional activity of microbes in human saliva appear rhythmic aside from a report that fails to detect these diurnal variations . Similar to the observations in mouse gut microbiota, an altered feeding schedule in humans impacts the diurnal fluctuation in microbiota abundance .…”
Section: Diurnal Oscillations In Microbiotamentioning
confidence: 69%